2023
DOI: 10.1039/d3nr00616f
|View full text |Cite
|
Sign up to set email alerts
|

Raman enhancement in bowtie-shaped aperture-particle hybrid nanostructures fabricated with DNA-assisted lithography

Abstract: We report on efficient surface-enhanced Raman spectroscopy (SERS) supporting substrates, which are based on deoxyribonucleic acid (DNA)-assisted lithography (DALI) and a layered configuration of materials. In detail, we used nanoscopic...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Recent studies have demonstrated the potential of combining top-down lithographic techniques with bottom-up (bio) chemical approaches to precisely control and position metallic nanoparticles and other biomaterials on macroscopic surfaces [12][13][14][15][16][17]. Of the various bottom-up methods, DNA origami nanotechnology has emerged as a promising approach for arranging nanoscale objects with a precision of 1-2 nm [13,[18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated the potential of combining top-down lithographic techniques with bottom-up (bio) chemical approaches to precisely control and position metallic nanoparticles and other biomaterials on macroscopic surfaces [12][13][14][15][16][17]. Of the various bottom-up methods, DNA origami nanotechnology has emerged as a promising approach for arranging nanoscale objects with a precision of 1-2 nm [13,[18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%